Thermophysical properties of methanol based Al2O3 nanofluids - Mostafizur, R.M.; Saidur, Rahman; Abdul Raman, Abdul Aziz; Bhuiyan, M.H.U. (Elsevier, 2015)
In this study, different volume concentrations (0.05, 0.10, 0.15, 0.20 and 0.25 vol) of cylindrical shaped Al2O3 nanopartides (50 nm length and 8 nm diameter) were suspended in methanol to produce methanol based nanofluid (MBNF). The nanofluid was prepared by using an ultrasonic homogenizer without any surfactants. Thermal conductivity (k), viscosity (mu) density (rho) and specific heat (C-p) of the nanofluid were measured for a wide range of temperatures (5, 10, 15, 20 and 25 degrees C). The k values in the range of 0.207-0.234 W/mK, mu values in the range of 0.70-0.94 mPas, rho values in the range of 791-814 kg/m(3) and C-p values in the range of 1.024-1.416 J/g degrees C were observed as the volume concentration increased from 0.05 to 0.25 vol with the temperature rising from 5 to 25 degrees C. The results showed that thermal conductivity, viscosity and density increased while specific heat decreased with increase in Al2O3 particle concentration. Besides, thermal conductivity and specific heat increased while viscosity and density decreased with increase in temperature. (C) 2015 Elsevier Ltd. All rights reserved.